أبو سُليمان الخَطّابيّومفهومُ الإعجاز القُرآنيّ: Abu Sulaiman AL-Khattabi and the Qura’anic Miracle - Humaidan, Qusay Salih Mutlag (SIBAWAYH Arabic Language and Education, 2021)
استَهدفَ البحثُ مفهومَ الإعجاز القرآني عند أبي سُليمان الخَطّابيّ (388هـ)، فتناولَ ما أُثِرَ في زمانه من نظرياتٍ ومفاهيم، بثّها في رسالته الموسومة: "بيان إعجاز القرآن"، وهي رسالة لطيفة في بابها. تركّزتِ الدّراسةُ على توثيق ما سَبقَ المؤلِّفَ من نظرياتٍ في مكامن الإعجاز القرآني، ناقشها بنقده الموضوعي، وحسِّه المرهف، وذوقه الصّادق، فرفضَ أن يكون وجهُ الإعجاز فكرةَ الصِّرفة، كما رفضَ قضيةَ الإخبار عن الغُيوب، وهكذا، ثُمّ أخذَ في بيان وجوه الإعجاز في نظم القرآن وتأليفه. إنّ مناقشة الآراء التي قيلتْ في الإعجاز وليستْ منه، وبيانَ عدم صحّتها ثُمّ رَفْضها، أوصلَه إلى نتائج عظيمةِ الأثر، كشفتْ عن وجهة نظره في فهم وجه الإعجاز. This research targeted the concept of Qura’anic miracle of Abi Sulaiman AL-Khattabi (388A.H). It handled the theories and concepts that were exposed in his time and implemented them in his thesis entitled: "Explaining the Qura’anic Miracles", which is a nice thesis in this field. The thesis focused upon documenting the theories revealed before the author’s time about the places of the Qura’anic miracle. He discussed them with his subjective critique, soft sense and honest sense. He refused the miracle to be the idea of inflection; he also rejected the issue of informing about hides. So, he started to reveal the miracle in the Qur’an systems and its authorization. The discussion of the views that have been said in the miracle which are not of it and the exploring that they are not true and reject them brought him to great impact results which revealed his point of view in understanding the miracle. Key words: AL-Khattabi, miracles, fields, Qura’anic